Recomendações para a realização de testes genéticos em cardiologia – revisão das principais diretrizes internacionais - Sousa, Alexandra (2020)
In recent years, the importance of genetic causes of cardiovascular diseases has been increasingly recognized, as the result of significant advances in molecular diagnosis techniques. This growing knowledge has enabled the identification of new phenotypes and the subclassification of clinical syndromes, impacting the therapeutic approach and genetic counseling offered to affected families. This paper describes the state of the art of genetic testing in the main cardiovascular diseases, aiming to provide a useful tool to help cardiologists and other health professionals involved in the care of individuals with hereditary heart diseases and their families.